ROLE OF ANTITHROMBIN IN DIAGNOSTICS AND INTENSIVE THERAPY OF ACUTE DIC-SYNDROME (review of literature and evidence of actual clinical practice) - N. A. VOROBIEVA («REMEDIUM GROUP» Ltd., 2017)
The article considers the issues of pathogenesis, diagnostics and intensive therapy of acute DIC-syndrome with underlying dysfunction of anticoagulant system. It also shows the role of early laboratory diagnostics of decreased antithrombin III activity for optimization of intensive therapy of acute DIC syndrome. The possibility of using antithrombin III concentrate has been demonstrated from the perspective of evidence-based medicine and real clinical practice.